Peran Ekowisata dalam Pemulihan Ekosistem Pesisir Kali Ciliwung - Pradini, Gagih; Fitria, Putri Maulida; Kusumaningrum, Anisa Putri; Ardani, Putri Aulia; Kausar, Devi Roza Krisnandhi (Peneliti.net, 2023)
The Ciliwung river area, which crosses the capital city of DKI Jakarta, has become an ecotourism and educational area in line with the improvement in water quality. This area has experienced various problems including coastal erosion, environmental damage, flooding, and poverty. In this case, it is necessary to work together between the government, the private sector, and the community to achieve a successful and sustainable recovery for the Ciliwung river coast. With the opening of ecotourism and educational tourism on the Ciliwung River, the general public to students can travel while learning the ins and outs, history and efforts to preserve the 120-kilometer river.